KEAHLIAN KEUANGAN KOMITE AUDIT DALAM MEMODERASI PENGARUH FRAUD TRIANGLE TERHADAP KECURANGAN LAPORAN KEUANGAN - Tania Larasati (2020)
The purpose of this study was to determine the affect of components such as Fraud Triangle including Financial Stability, External Pressure, Financial Target, Ineffective Monitoring and Rationlization toward Financial Statement Fraud. This research also using the audit Committee's Financial Expertise as a Moderating variable. In this research, the dependent variable has using method named F-Scores was introduced by Dechow et al., (2007). The population in this research are manufacturing companies listed on the Indonesia Stock Exchange for the period 2016 - 2018. The number of samples are 225 sampels. The methods used in this research is quantitative method by analyzing two panel data, regression models, the classic assumption feat, the coefficient of determination and the last method named partially test (t test). This research use the progam data named STATA version 13. The result from this research said that are External Pressure and Rationalization have a negative affects on Financial Statement Fraud. However variable Financial Stability, Financial Target, and Ineffective Monitoring have no affects to Financial Statement Fraud. Meanwhile, for moderation variable, the Audit Committee's Financial Expertise can moderate the influence of external pressure, financial target, and rationalization toward Financial Statement Fraud.